Evaluasi terapi erytropoetin pada pasien hemodialisa di rumah sakit PKU Muhammadiyah Yogyakarta - Adnan, Adnan; Dania, Haafizah; Supadmi, Woro (Universitas Ahmad Dahlan, 2018)
Most of the patients with end-stage renal disease who undergoing hemodialysis received erythropoietin (EPO) therapy for the anemia treatment. Deficiency anemia erythropoietin is a common complication of chronic kidney disease (CKD). EPO therapy is expected to improve the anemia and can improve the quality of life of patients.This study was conducted in an analytic observational with Cross Secsional design. The purpose of this study was to know there was a difference of red blood cell profile involve hemoglobin (Hb), Mean Corpusculair Volume (MCV), Mean Corpusculair Haemoglobin (MCH), Mean Corpusculair Haemoglobin Concentration (MCHC) and quality of life of CKD patients who received EPO and non EPO therapy in PKU Muhammadiyah Yogyakarta Hospital. Inclusion criteria in this study were PGK ICD N18.9 patients who were undergoing hemodialysis therapy at RS PKU Muhammadiyah Yogyakarta, outpatient, can read and understand the questionnaire, and accept to be a respondent.The results of this study showed no significant difference (p>0,05) in red blood cell (Hb, MCV, MCH, MCHC) between EPO and non EPO therapy groups. The associated of EPO with the quality of life of patients in all of KDQOL domains was p> 0.05.The conclusions of this study showed that there was no significant difference between EPO and Non EPO therapy and there was no correlation between EPO and non EPO therapy with quality of life of hemodialysis patients.